The evaluation model of construction companies’ personnel safety and health system - Dejus, Titas; Viteikiene, Milda (Technological and Economic Development of Economy, 2004)
When the economy in the country grows up and strengthens (currently the growth rates of the economy are the highest among three Baltic States), at the same time one of the most important business areas intensively develops. Sometimes it is called as the indicator of the country’s economical situation ‐ construction. The facts given by the Statistics Department suggest that BVP in the second quarter of 2003 grew 9,1%, while erection working coverage in construction ‐ about 13,8 %. And if we evaluate the economic inertia influence on the construction business and the bias of accounting (not evaluated yet) ‐ we can expect even greater growth of the real coverage [1], which (the growth) as predicted will last for several years. When analyzing accidents according to harmful factors at work, we can see that a quarter of them happens when a man falls down from altitude, the sixth ‐ when he falls down due to slip, the tenth ‐ because of the active gear, mechanism, etc. Facts are shown about the accidents at work according to the factors in 2002. Article in Lithuanian. Statybos įmonių darbuotojų saugos ir sveikatos sistemos vertinimo modelis First Published Online: 21 Oct 2010